Antibody production and tolerance to the α-gal epitope as models for understanding and preventing the immune response to incompatible ABO carbohydrate antigens and for α-gal therapies - Uri Galili (Frontiers in Molecular Biosciences, 2023)
This review describes the significance of the α-gal epitope (Galα-3Galβ1-4GlcNAc-R) as the core of human blood-group A and B antigens (A and B antigens), determines in mouse models the principles underlying the immune response to these antigens, and suggests future strategies for the induction of immune tolerance to incompatible A and B antigens in human allografts. Carbohydrate antigens, such as ABO antigens and the α-gal epitope, differ from protein antigens in that they do not interact with T cells, but B cells interacting with them require T-cell help for their activation. The α-gal epitope is the core of both A and B antigens and is the ligand of the natural anti-Gal antibody, which is abundant in all humans. In A and O individuals, anti-Gal clones (called anti-Gal/B) comprise >85% of the so-called anti-B activity and bind to the B antigen in facets that do not include fucose-linked α1–2 to the core α-gal. As many as 1% of B cells are anti-Gal B cells. Activation of quiescent anti-Gal B cells upon exposure to α-gal epitopes on xenografts and some protozoa can increase the titer of anti-Gal by 100-fold. α1,3-Galactosyltransferase knockout (GT-KO) mice lack α-gal epitopes and can produce anti-Gal. These mice simulate human recipients of ABO-incompatible human allografts. Exposure for 2–4 weeks of naïve and memory mouse anti-Gal B cells to α-gal epitopes in the heterotopically grafted wild-type (WT) mouse heart results in the elimination of these cells and immune tolerance to this epitope. Shorter exposures of 7 days of anti-Gal B cells to α-gal epitopes in the WT heart result in the production of accommodating anti-Gal antibodies that bind to α-gal epitopes but do not lyse cells or reject the graft. Tolerance to α-gal epitopes due to the elimination of naïve and memory anti-Gal B cells can be further induced by 2 weeks in vivo exposure to WT lymphocytes or autologous lymphocytes engineered to present α-gal epitopes by transduction of the α1,3-galactosyltransferase gene. These mouse studies suggest that autologous human lymphocytes similarly engineered to present the A or B antigen may induce corresponding tolerance in recipients of ABO-incompatible allografts. The review further summarizes experimental works demonstrating the efficacy of α-gal therapies in amplifying anti-viral and anti-tumor immune-protection and regeneration of injured tissues.